Across Waters - The river redesigned Belgrade, Serbia (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2016)
This essay presents a significant selection of town and architecture design models developed on-and-for the Danube during the scientific cooperation held in the years 2008-2012 in the University of Belgrade and Sapienza University of Rome2. The subject of this modeling action on Belgrade and the Danube river is design along the banks of a river of continental size as it flows through a city that has, historically, and in fact, the rank of a capital town. The complete report of the action was published by the same author of this essay in Rome with the title â€œAcross Waters â€“ Il fiume riprogettatoâ€ in the year 2012. The cooperation is still working today, nearly ten years after its establishment, on further pilot areas along the Danube.